OVERCOMING CHALLENGES IN PROJECT-BASED LEARNING: INSIGHTS FROM EFL LEARNERS AND EFFECTIVE STRATEGIES FOR SUCCESS - Zainina Zahwa Amalia; Dewi Nur Rizqi Fatmala; Dira Aprilia Nanda; Lilia Indriani (Universitas Islam Ogan Komering Ilir Kayuagung, 2023)
This study examined the English Education Department's projectbased learning challenges and methods. In order to obtain insight into their experiences, the study concentrated on sixth-semester students enrolled at a state institution in Central Java. In conducting this research, qualitative data was used with a case study approach design. To gather the required data, a questionnaire is the data collection instrument used. Several challenges were found, such as difficulty finding theories and previous research related to their project, time management, and overlapping with other lecture assignments. Students then give their strategies to deal with that obstacle by collaborating with peers, breaking down the project into smaller ones to help avoid being overwhelmed, and setting goals and timelines for the project using a calendar planner